HISTORY EDUCATION AS A MEANS OF FORMING STUDENT IDENTITY AT SMAN 2 MEDAN - Akla, Abul; Sumantri, Pulung; Aisyah, Sitti (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This study aims to examine the role of history education in the formation of student identity at SMA Negeri 2 Medan. Using a qualitative approach with case study design, data were collected through in-depth interviews, classroom observations, and documentation studies. The results of the study show that history education at SMA Negeri 2 Medan has an important role in shaping students' identities, especially in instilling national and cultural values. History teachers use varied and contextual learning methods, such as discussions, debates, and interactive learning resources, which have proven to be effective in increasing student participation and understanding. However, the study also found challenges such as limited learning time and students' lack of interest in history. Nevertheless, history education still has a positive impact in strengthening students' identities as Indonesia citizens with integrity and a strong sense of nationality. Research recommendations include innovation of learning methods, increased time allocation, and provision of adequate learning resources to optimize the role of history education in the formation of students' identity.